Single-Nucleotide Polymorphism Array Technique Generating Valuable Risk-Stratification Information for Patients With Myelodysplastic Syndromes - Xiao, Xia; He, Xiaoyuan; Li, Qing; Zhang, Wei; Zhu, Haibo; Yang, Weihong; Li, Yuming; Geng, Li; Liu, Hui; Li, Lijuan; Wang, Huaquan; Fu, Rong; et al. (Frontiers in Oncology, 2020)
Background: Chromosomal abnormalities play an important role in the diagnosis and prognosis of patients with myelodysplastic syndromes (MDSs). The single nucleotide polymorphism array (SNP-A) technique has gained popularity due to its improved resolution compared to that of metaphase cytogenetics (MC) analysis. Methods: A total of 376 individuals were recruited from two medical centers in China, including 350 patients and 26 healthy individuals. Among these patients, 200 were diagnosed with de novo MDSs, 25 with myeloproliferative neoplasms (MPNs), 63 with primary acute myeloid leukemia (AML) and 62 with idiopathic cytopenia of undetermined significance (ICUS). We evaluated the significance of abnormal chromosomes detected by SNP-A in the diagnosis and prognosis of MDS-related disorders. Results: (1) When certain chromosomal abnormalities could not be detected by conventional MC methods, these abnormalities could be detected more efficiently by the SNP-A method. With SNP-A, the detection rates of submicroscopic or cryptic aberrations in the MDS, MPN and AML patients with normal MC findings were 32.8%, 30.8% and 30%, respectively. (2) The chromosomal abnormalities detected by SNP-A had a very important value for the prognosis of patients with MDSs, especially in the low-risk group. The survival of patients with abnormal chromosomes detected by SNP-A was significantly lower than that of patients with no detected chromosomal abnormalities; this difference was observed in OS (P=0.001) and PFS (24 months vs NR; P=0.008). The patients with multiple chromosomal abnormalities detected by SNP-A had an inferior prognosis, and SNP-A abnormalities (≥3 per patient) were found to be an independent predictor of poor prognosis in patients with MDSs (HR=2.40, P=0.002). (3) Patients with ICUS may progress to myeloid malignancies, but most patients often maintain a stable ICUS status for many years without progression. An ICUS patient found to have an MDS-related karyotype would be rediagnosed with MDS. SNP-A can efficiently detect chromosomal abnormalities, which would be important for assessing the evolution of ICUS. In our study, 17 ICUS patients with SNP-A-detected abnormalities developed typical MDSs. Conclusions: SNP-A can help evaluate the prognosis of patients with MDSs and better assess the risk of disease progression for patients with ICUS.